Estudio de germinación y crecimiento de especies nativas en presencia-ausencia de hongos micorrícicos con fines de restauración ecológica - Becerril Navarrete, Arubi Monserrat (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
In the last few years, in forestry ecosystems, anthropogenic agents or natural disturbances have increased, some of these are linked to climate change, which has resulted in the loss of ecosystem services. Therefore, ecological restoration is a key tool for the management, conservation and restoration of ecosystems in front of climate change. However, in forest ecosystems information is still lacking, mainly for the disturbed sites restoration; the usage and germination of native species with mycorrhizae is an alternative to increase the success in restoring sites. The shrubs species Monnina ciliolata DC (with blue-purple flowers, native in temperate forests) and Tecoma stans (L.) Juss ex Kunth (1-10 meters tall) are considered restoration potential species. For their establishment, it is proposed to use of mycorrhizal fungi, due to their positive effect on growth and survival. The objectives in the present work are to know the effect of pregerminative treatments and evaluate the mycorrhizal interaction and a plant bacterium in M. ciliolata and T. stans plants. The germination experiment consisted of four treatments and a control with 30 replicates for Monnina and, a treatment and control with 100 replicates (Tecoma), with one seed per container in a mixture of peat-moss-agrolite (70% -30%), irrigation to field capacity and evaluation every third day. Germination speed and percentage were obtained. For the mycorrhizal interaction, one seed was placed per container and inoculated with a mixture of coco fiber-agrolite substrate (70% -30%), three treatments and one control (30 replicates in Monnina) and for Tecoma, five treatments and a control (50 replicates). Were evaluated for a six months period; by destructive method, aerial and radical biomass, among other variables. As results: in M. ciliolata germination began on day 21 in control treatment with 63% and germinated T. stans in nine days with 83%.

En los ecosistemas forestales, en los últimos años han aumentado agentes de disturbio antropogénico o natural, algunos de estos ligados al cambio climático, generando la pérdida de servicios ecosistémicos. Ante ello, la restauración ecológica es clave para el manejo, conservación y restauración de ecosistemas frente al cambio climático. Sin embargo, falta información para la restauración de sitios perturbados; el uso y germinación de especies nativas, junto con las micorrizas. Las especies de arbustos Monnina ciliolata DC. (con flores azul-moradas, nativa de bosques templados) y Tecoma stans (L.) Juss exKunth (1-10 m de altura) se consideran especies con alto potencial para restauración. Para su establecimiento se propone utilizar hongos micorrícicos, por su efecto positivo en el crecimiento y supervivencia. Los objetivos de este estudio son conocer el efecto de tratamientos pregerminativos y evaluar la interacción de diversos hongos micorrícicos, y la adición de una bacteria en plantas de M. ciliolata y T. stans. El experimento de germinación fue de cuatro tratamientos y control; (30 semillas en Monnina) y, un tratamiento y control (100 réplicas en Tecoma), con una semilla por contenedor en una mezcla de turba- agrolita (70%-30%), riego a capacidad de campo y evaluación cada tercer día. Se obtuvo velocidad y porcentaje de germinación. Para la interacción micorrícica, se colocó una semilla por contenedor y se inoculó, se establecieron tres tratamientos y un control (30 réplicas) en Monnina y para Tecoma, cinco tratamientos y un control (50 réplicas), en fibra de coco-agrolita (70%-30%). Se evaluó por seis meses; por método destructivo se evaluó biomasa aérea y radical, entre otras variables. Como resultados: inició la germinación en M. ciliolata el día 21 en el control (63%) y en T. stans inició a los nueve días (83%).
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FB-M-2021-0276; Inoculación; Micorrización; Arbusto; Interacción; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6391